Pharmacists delivering hypertension care services: a systematic review and meta-analysis of randomized controlled trials - Gastens, Viktoria; Tancredi, Stefano; Kiszio, Blanche; Del Giovane, Cinzia; Tsuyuki, Ross T.; Paradis, Gilles; Chiolero, Arnaud; Santschi, Valérie (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCommunity-based models of care with the involvement of pharmacists and other nonphysician healthcare professionals can help improve blood pressure (BP) control. We aimed to synthesize the evidence of effectiveness of pharmacist interventions on BP among patients with hypertension.MethodsWe performed systematic searches to identify randomized controlled trials (RCTs) assessing the effect of pharmacist interventions on BP among outpatients (latest search, March 2024). The effect on systolic and diastolic BP change or BP control were pooled using random effects model. Subgroup analysis for the types of pharmacist interventions and healthcare settings were performed. The risk of bias was assessed using the Cochrane Risk of Bias Tool 2. The protocol was registered in PROSPERO (CRD42021279751) and published in an open-access peer-reviewed journal.ResultsOut of 2,330 study records identified in 7 electronic databases, a total of 95 RCTs, with 31,168 participants (control 16,157, intervention 15,011), were included. The intervention was led by the pharmacist in 75% of the studies and in collaboration with other healthcare providers in 25%. Pharmacist interventions included patient education in 88%, feedback to healthcare providers in 49%, and patient reminders in 24% of the studies. Systolic and diastolic BP were reduced after pharmacist intervention by −5.3 mmHg (95% CI: −6.3 to −4.4; I2 = 86%) and −2.3 mmHg (95% CI: −2.9 to −1.8; I2 = 75%), respectively. The reduction of systolic BP tended to be larger if the intervention was collaborative, conducted in outpatient clinics, based on healthcare provider education, or through healthcare provider feedback. Analyses restricted to relatively large or high-quality studies yielded similar estimates, with lower between-studies heterogeneity.ConclusionPharmacist care for patients with hypertension consistently improves BP across various settings and interventions. Pharmacist care is one key element of the solution to the global burden of hypertension and cardiovascular diseases. PROSPERO registration numberCRD42021279751.